One Shoot, Two Birds: Alleviating Inflammation Caused by Ischemia/Reperfusion Injury to Reduce the Recurrence of Hepatocellular Carcinoma - Chen, Hao; Lu, Di; Yang, Xinyu; Hu, Zhihang; He, Chiyu; Li, Huigang; Lin, Zuyuan; Yang, Modan; Xu, Xiao (Frontiers in Immunology, 2022)
Inflammation is crucial to tumorigenesis and the development of metastasis. Hepatic ischemia/ reperfusion injury (IRI) is an unresolved problem in liver resection and transplantation which often establishes and remodels the inflammatory microenvironment in liver. More and more experimental and clinical evidence unmasks the role of hepatic IRI and associated inflammation in promoting the recurrence of hepatocellular carcinoma (HCC). Meanwhile, approaches aimed at alleviating hepatic IRI, such as machine perfusion, regulating the gut-liver axis, and targeting key inflammatory components, have been proved to prevent HCC recurrence. This review article highlights the underlying mechanisms and promising therapeutic strategies to reduce tumor recurrence through alleviating inflammation induced by hepatic IRI.